Do Taxes Matter in the CAPM? - Lutz Kruschwitz; Andreas Löffler (BuR - Business Research, 2009)
The traditional literature on the CAPM assumes that investor's tax payments simply vanish from the model. This assumption is not at all consistent with the actual behavior of the Treasury. The theory of general equilibrium states that an interest rate rf = 0 will not affect prices if taxes are introduced. We show that this result can be extended to the CAPM if the tax payments are redistributed among investors.
urn:nbn:de:0009-20-21644
Keywords: 650; CAPM; CARA utility; Tax-CAPM; equilibrium; taxes; CAPM; Gleichgewicht; Steuer; Nutzenfunktion; Theorie